Synergic Antibacterial Effect of Curcumin with Ampicillin; Free Drug Solutions in Comparison with SLN Dispersions - Faezeh Alihosseini; Shirzad Azarmi; Solmaz Ghaffari; Setareh Haghighat; Seyed Mahdi Rezayat Sorkhabadi (Tabriz University of Medical Sciences, 2016)
Purpose: This study was designed to investigate benefit of using nanotechnology on increasing of synergic antibacterial effect of natural and chemical antibacterial agents. Methods: At first the MIC and MBC of Curcumin and Ampicillin as selected antibacterial agents was determined, after that Solid Lipid Nanoparticles (SLNs) of each active ingredients as well as Curcumin-Ampicillin loaded SLNs were prepared using high pressure homogenization technique. Characterization of prepared SLNs was done, then MIC, MBC and contact killing time were investigated for Curcumin-Ampicillin loaded SLNs in comparison with free Curcumin and Ampicillin solutions as well as Ampicillin and Curcumin SLNs. Results: Based on results nanoparticles with the size of 150 nm show much more decreased MIC and MBC when Ampicillin and Curcumin were loaded together on SLNs than solutions in which free Ampicillin and Curcumin were mixed. Conclusion: It seems that using nanotechnology could cause decrease the dosage of antibiotics and risk of having antibiotic resistance bacteria strains.